Odpowiedzi

2010-03-15T15:53:49+01:00
0,2x+0,3=-0,5 \-0,3
0,2x=-0,8 \:0,2
x=-0,25

0,4+0,25x=-2 \-0,4
0,25x=-2,4 \:0,25
x=0,10

2,1-0,3x=0,4x \-2,1
-0,3x=-1,7 \:(-0,3)
x=0,17


i w taki sposób do końca;)
Pozdrawiam
2010-03-15T15:57:45+01:00
A)0,2x+0,3=-0,5
0,2x=-0,5-0,3
0,2x=-0,8
x=-4
b)0,4+0,25x=-2
0,25x=-2-0,4
0,25x=-2,4
x=9,6
c)2,1-0,3x=0,4x
-0,3x-0,4x=-2,1
-0,7x=-2,1
x=3
d)-1,5x-3=0,2x+6
-1,5x-0,2x=6+3
-1,7x=9
x=-9/1,7
x=-5całych i 0,5/1,7
e)1/2x-4=x-6
1/2x-x=-6+4
-1/2x=-2
x=4
f)x-5=1/3x+1
x-1/3=1+5
2/3x=6
x=9
g)x/4-1/4=2
h)x/5-3=x+1/5
i)5/6(x-1)=4
5/6x-5/6=4
5/6x=4+5/6
5/6x=29/6
x=5/29
j)-1/2(-x-6)=-x
-1,2x+3=-x
-1,2x+x=-3
0,5x=-3
x=6